1977
DOI: 10.1111/j.1600-0773.1977.tb02060.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lithium on Water Binding Ability, Consistency and Macromolecules in the Rat Brain

Abstract: Abstruci: Wistar male rats were treated with lithium for 50, 80, and 120 days, respectively. Lithium was added to the diet (40 mmol/kg of diet), the plasma lithium concentration being in the range of 0.55-0.70 mmol/l of plasma. The treatment caused a significantly more rigid consistency of the brain tissue. The water content and water binding ability in various parts of the brainmeasured by a drying coursewas unchanged. The content of hexosamine and protein in total brains was significantly decreased (about 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…These authors suggest that the altered staining properties are the result of changes in the mucoproteins and the mucopolysaccharides of the intercellular matrix. Edelfors (1977) supported these histological findings by demonstrating an increased content of hyaluronic acid in the brains from chronically lithium-treated rats. Dawson & Whittam (1970) found that replacement of external sodium by lithium caused an inhibition of the '2P-pump component resulting in a decreased ATP-synthesis.…”
Section: Discussionsupporting
confidence: 55%
“…These authors suggest that the altered staining properties are the result of changes in the mucoproteins and the mucopolysaccharides of the intercellular matrix. Edelfors (1977) supported these histological findings by demonstrating an increased content of hyaluronic acid in the brains from chronically lithium-treated rats. Dawson & Whittam (1970) found that replacement of external sodium by lithium caused an inhibition of the '2P-pump component resulting in a decreased ATP-synthesis.…”
Section: Discussionsupporting
confidence: 55%
“…Lithium, however, is known to have an effect on multiple neuronal systems, an effect which is partly on hormone-sensitive adenylate cyclase systems (Geisler & Klysner 1981), partly on the calcium-inositol system (Hallcher & Sherman 1980), and partly a more general membrane "stabilizing" effect (Edelfors 1977;Andersen et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…So far there have been no investigations as to the glycopeptide content in the cerebrospinal fluid from manic-depressive patients, but schizophrenia and manicdepressive psychosis are both endogenous disorders where abnormal function of the central nervous system can be expected. The increased content of sialogangliosides and sialoglycopeptides may be another expression of general membrane changes caused by the lithium treatment and which may be of importance for the therapeutical effect (Wagner et al 1970;Edelfors 1977Edelfors & 1980.…”
Section: Controlsmentioning
confidence: 99%